ANTIFOULING ACTIVITY OF BACTERIA ASSOCIATED WITH SOFT CORAL Sarcophyton sp. AGAINST MARINE BIOFILM-FORMING BACTERIA - Agus Sabdono; Ocky Karna Radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Marine bacteria associated with soft coral Sarcophyton sp collected from vicinity of Peucang island, Ujung Kulon, West Java, were successfully screened for antifouling activity against marine biofilm-forming bacteria isolated from the surrounding colonies of Sarcophyton sp. Six bacterial isolates were found to inhibit the growth of at least one of 7 biofilm-forming isolates. The most active strain USP3.37 was identified as Pelagiobacter variabilis by using 16S rDNA gene sequence analysis. Similarly, the active strains USP3.3, USP8.43, USP3.12, USP3.16 and USP8.6 were identified as Arthrobacter nicotianae, Shewanella alga, Pseudomonas synxantha, Pseudomonas falgida, Pseudovibrio denitrificans and Bacillus aquamaris, respectively. USP3.37 strain was found to amplify gene fragments of non-ribosomal peptide synthetase (NRPS). This raises the possibility the use of softcoral bacteria as the source of antibacterial compounds for controlling the antifouling in the sea. Therefore, this bacterium would be better to select eco-friendly antifouling compounds than the other antibacterial activities.